2007
DOI: 10.1002/ijc.23096
|View full text |Cite
|
Sign up to set email alerts
|

Nm23‐H1 expression of metastatic tumors in the lymph nodes is a prognostic indicator of oral squamous cell carcinoma

Abstract: We recently reported that low Nm23-H1 expression of primary oral squamous cell carcinoma (OSCC) was correlated with the occurrence of lymphatic metastasis. However, little is known about whether Nm23-H1 level of metastatic tumors in the cervical lymph nodes is reduced in comparison with primary oral cancers and its significance for patients' prognosis. By immunohistochemistry, we analyzed the Nm23-H1 expression in 52 pairs of OSCC specimens from primary oral cancers and their metastatic lymph nodes. Western bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 37 publications
2
23
0
Order By: Relevance
“…Remarkably, enforced NME1 expression induced by transfection in epithelial cancer derived cell lines and melanoma reverses their motility and invasive potential. This was observed with cell lines derived from melanoma (Leone et al, 1991) and from breast (Leone et al, 1993a), colon (Suzuki et al, 2004), lung (Nie et al, 2008), liver (She et al, 2010), ovarian (Li et al, 2006), prostate (Andolfo et al, 2011) and oral (Wang YF et al, 2008) carcinomas. In other types of cancers such as neuroblastoma (Leone et al, 1993b;Garcia et al, 2012), hematopoietic malignancies (Yokoyama et al, 1998) and osteosarcoma (Liao et al, 2000), a high tumoral expression was noted which was most often correlated with poor clinical outcome.…”
Section: Homologymentioning
confidence: 86%
See 2 more Smart Citations
“…Remarkably, enforced NME1 expression induced by transfection in epithelial cancer derived cell lines and melanoma reverses their motility and invasive potential. This was observed with cell lines derived from melanoma (Leone et al, 1991) and from breast (Leone et al, 1993a), colon (Suzuki et al, 2004), lung (Nie et al, 2008), liver (She et al, 2010), ovarian (Li et al, 2006), prostate (Andolfo et al, 2011) and oral (Wang YF et al, 2008) carcinomas. In other types of cancers such as neuroblastoma (Leone et al, 1993b;Garcia et al, 2012), hematopoietic malignancies (Yokoyama et al, 1998) and osteosarcoma (Liao et al, 2000), a high tumoral expression was noted which was most often correlated with poor clinical outcome.…”
Section: Homologymentioning
confidence: 86%
“…McDonald et al (1996) have shown that a high NME1 expression in the primary tumor predicts a favorable outcome although the reverse was found by another study (Pavelic et al, 2000). Wang YF et al (2008) have observed a low NME1 level in lymph node metastases of patient with oral squamous cell carcinoma and that induced NME1 overexpression in these cancer derived cell lines decreased their invasive potential. In osteosarcoma, a positive immunoreactivity was detected in tumoral cells (Oda et al, 1995;Liao et al, 2000), but no correlation (Liao et al, 2000;Ozger et al, 2009) or a positive correlation (Oda et al, 2000) between NME1 expression and metastatic spread was observed.…”
Section: Other Cancersmentioning
confidence: 99%
See 1 more Smart Citation
“…The prognostic potential of biomarker expression in the different tumor components of lymph node positive cancer has been compared in only few tumors [19][20][21] including prostate cancers [22][23][24][25]. In case of successful survival stratification, the metastasizing tumor component but not the primary tumor [19,20,22] or both tumor components [21,23,25] may harbor the prognostic information.…”
Section: Discussionmentioning
confidence: 99%
“…Candidates for biomarkers of head and neck cancers including oral SCC (OSCC) were found in some studies; however, they have not been of practical use. 4,5 Although diagnostic imaging, status of lymph node metastasis and histology still will be clinically essential criteria, they are not able to provide sufficient information to realize the individualized treatment of OSCC in the future. A precise malignancy diagnosis of OSCC, such as prediction of potential metastasis or accurate assessment of treatment sensitivity at the early stage prior to revealing the existence of metastatic focus, enables us to set proper ranges of resection and to plan surgical methods.…”
mentioning
confidence: 99%